Juurten paleltumiselle kynnysarvot - Poteri, Marja (Metsäntutkimuslaitos, 2002)
Selostus artikkelista: Dumais Daniel, Coursolle Carole, Bigras Francine J. ja Margolis Hank A. 2002. Simulated root freezing in the nursery: effects on the growth and physiology of containerized boreal conifer seedlings after outplanting. Canadian Journal of Forest Research 32: 605–615.
Julkaisusatoa